2018
DOI: 10.1615/jenvironpatholtoxicoloncol.2018028689
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Mitochondrial Respiratory Dysfunction during Hexavalent Chromium-Induced Lung Carcinogenesis

Abstract: Hexavalent chromium [Cr(VI)] is a lung carcinogen and its complete mechanism of action remains to be investigated. Metabolic reprogramming of key energy metabolism pathways (e.g., increased anaerobic glycolysis in the presence of oxygen or “Warburg effect,” dysregulated mitochondrial function, and lipogenesis) are important to cancer cell and tumor survival and growth. In our current understanding of Cr(VI)-induced carcinogenesis, the role for metabolic reprogramming remains unclear. In this study, we treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Hexavalent chromium (Cr +6 ) compounds are classified as carcinogenic to humans in the respiratory tract, giving rise to cancer of the lungs, nose, and nasal sinuses. It is mutagenic when inhaled and also potentially when ingested orally in large quantities [104,105]. In particular, in certain occupational environments, workers may suffer from inhalation exposure by Cr +6 dust, mists, and fumes [106].…”
Section: Carcinogenic Risk Assessmentmentioning
confidence: 99%
“…Hexavalent chromium (Cr +6 ) compounds are classified as carcinogenic to humans in the respiratory tract, giving rise to cancer of the lungs, nose, and nasal sinuses. It is mutagenic when inhaled and also potentially when ingested orally in large quantities [104,105]. In particular, in certain occupational environments, workers may suffer from inhalation exposure by Cr +6 dust, mists, and fumes [106].…”
Section: Carcinogenic Risk Assessmentmentioning
confidence: 99%
“…Since metal AM involve both ultrafine and fine metal particles, and in general similar elements as can be found in metal production environments, it could be expected that AM operators have similar exposure related health risks as other metalworkers [7,8]. For example, lung complications have been found in hard metalworkers due to cobalt, hexavalent chromium, and nickel exposure [9][10][11], which may be relevant since cobalt, nickel, and chromium (but not hexavalent) are common components in AM powders. Also, lung function and cardiovascular disease (CVD) risk among welders have been extensively studied [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Both the BEP2D and Cr(VI)-transformed BEP2D cell lines were cultured in LHC-8 media. All cells were screened for growth in soft agar and in nude mice to confirm the Cr(VI)-transformed cells and passage-matched control cells; this confirmed that the passagematched control cells did not spontaneously transform [12]. Additionally, karyotypes were screened by Dr. John P. Wise, Sr. at the University of Louisville, KY to authenticate the passage-matched control cell lines.…”
Section: Cell Culturementioning
confidence: 94%
“…Using the BEAS-B cells and Cr(VI)-transformed BEAS-2B cells (B2B-CrT) from our previous study, we investigated lipogenesis endpoints in these cells (protein and functional palmitic acid levels) [12]. The B2B-CrT cells had increased ACLY, pACLY, ACC1, and FASN protein expressions compared to passage-matched control BEAS-2B cells.…”
Section: Chromium(vi)-transformed Beas-2b Cells Have Increased Lipoge...mentioning
confidence: 99%
See 1 more Smart Citation